(untitled) (University Journal of Zoology, Rajshahi University, 2009)
The electrophoretic banding pattern of esterase isozymes were examined in eighteen different tissues of Nile tilapia after staining with Î± and Î² naphthyl acetate as substrate. The tissues were anterior-, mid-, tailmuscle (ventral and tip region), buccal muscle, stomach, fore-, mid-, hind-gut, liver, gill, heart, kidney, eye (lens), eye (iris), fore-, mid- and hind- brain. Altogether five bands named as Est-11.4, Est-21.1, Est-31, Est-40.62 and Est-50.25 were observed different relative mobility. Est-1 and Est-5 denote the fastest and slowest band. Est-3 was present in all the tissues. All five bands were expressed in liver and stomach. Some of the esterase bands showed tissue and substrate specificity, where Est-1 was in fore-, mid- and hind- brain, Est-2 in hind gut, Est-5 in stomach, gill and heart was stained only with Î± naphthyl acetate. None of the band was expressed with Î² naphthyl acetate only. Key words: esterase, isozyme, Oreochromis, tissue Â Doi:10.3329/ujzru.v27i0.1942 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 01-05